Prevalence of microdontia among orthodontic patients of Kathmandu, Nepal - Gupta, Sanjay Prasad; Dahal, Samarika; Rauniyar, Shristi (Journal of Karnali Academy of Health Sciences, 2024)
Background: Microdontia is a condition where the teeth are smaller than the normal size, which may involve all teeth or be limited to a single tooth or a group of teeth. The objective of this study was to find out the prevalence of microdontia among orthodontic patients of Kathmandu, Nepal. Methods: In this cross-sectional study, 390 orthodontic casts of patients (166 males and 224 females) who came for orthodontic treatment between the age of 14 to 22 years (mean age of 17.434.28 years) were selected. The mesiodistal dimension of each tooth was recorded with the help of digital vernier caliper. A tooth was diagnosed as microdontia when it is smaller than the normal size. Data analysis was performed using SPSS version 21.0 with a confidence level set at 95% (P<0.05). Chisquare test was used to determine the difference in prevalence of microdontia among the genders. Whereas, mesio-distal dimensions of teeth were compared on both sides of the jaws using student’s t-test. Results: The prevalence of overall microdontia was 6.66% (26) whereas prevalence of single tooth microdontia, multiple teeth and generalized microdontia was 2.3% (9), 2.83% (11) and 1.53% (6) respectively. There was no statistical difference in the prevalence of microdontia among genders (p=0.987). In addition, there was no statistical difference in the mesio-distal dimensions of teeth on both sides of the jaws (p>0.05). Conclusion: Microdontia was one of the common dental anomalies present among the orthodontic patients. The most common tooth affected by microdontia was maxillary lateral incisor and microdontia affects the maxillary teeth more than the mandibular teeth. There was no statistically significant difference in prevalence of microdontia among genders